On Early Jewish Literature and the Aramaic Magic Bowls - Bhayro, Siam (Aramaic studies, 2015)
This article discusses examples of ‘lost midrashim’ that occur in both the New Testament and the Aramaic magic bowls, with a view to demonstrating the significance of the magic bowls for the study of early Jewish literature.